2006
DOI: 10.1002/elps.200600088
|View full text |Cite
|
Sign up to set email alerts
|

Numerical model for DNA loading in microdevices: Stacking and autogating effects

Abstract: Many electrophoresis-based DNA sequencing and genotyping microdevices rely on field-driven effects to load and preconcentrate the sample. A quantitative model is developed for a broad class of electrophoresis-based microfabricated sample injectors. Quantitative predictions of DNA preconcentration are compared with experimental data and are shown to qualitatively reproduce the detailed time-evolving sample distribution in the injector. The model provides practical guidance on device and protocol design, in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…While 5 lL sample aliquots were used for the majority of this work, the intensity of the product peaks was observed to scale with the amount of sample initially loaded onto the spin-column, increasing linearly from 1 to 10 lL. Consistent with previous reports relating the injection conditions to the relative concentrations of injected DNA fragments, 20 it was observed that a 30 s injection at 500 V cm −1 resulted in increased product being introduced into the analysis channel. This was due to stacking at the DNA-buffer interface.…”
Section: Resultssupporting
confidence: 78%
“…While 5 lL sample aliquots were used for the majority of this work, the intensity of the product peaks was observed to scale with the amount of sample initially loaded onto the spin-column, increasing linearly from 1 to 10 lL. Consistent with previous reports relating the injection conditions to the relative concentrations of injected DNA fragments, 20 it was observed that a 30 s injection at 500 V cm −1 resulted in increased product being introduced into the analysis channel. This was due to stacking at the DNA-buffer interface.…”
Section: Resultssupporting
confidence: 78%
“…1). The first of these [1] is at the “gel” interface in the sample well (analogous to CAE). The second [2,7,8] is at the parting intersection of the loading arm and the separation channel, where a second conductivity discontinuity can be induced using ion depletion with pre-loading currents and low-conductivity buffer.…”
Section: Resultsmentioning
confidence: 99%
“…Even without high injection voltages Aborn [3] showed that careful conditioning of the first and second interfaces using pre-loading currents could be used to achieve routine injections into a 768-lane microdevice sequencer with a factor of eight reduction in required sample mass relative to contemporary CAE Sanger sequencing. Stacking and autogating effects at the first interface, which confound the experimental reproducibility, were reproduced accurately by a numerical model [1]. In practice, the uniform conditioning of both the first and second stacking interfaces is among the very most important aspects needed to get uniform results out of an cross-injected array microdevice [3].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations